2004
DOI: 10.1021/ja039615x
|View full text |Cite
|
Sign up to set email alerts
|

Why Is CO2 So Soluble in Imidazolium-Based Ionic Liquids?

Abstract: Experimental and molecular modeling studies are conducted to investigate the underlying mechanisms for the high solubility of CO2 in imidazolium-based ionic liquids. CO2 absorption isotherms at 10, 25, and 50 degrees C are reported for six different ionic liquids formed by pairing three different anions with two cations that differ only in the nature of the "acidic" site at the 2-position on the imidazolium ring. Molecular dynamics simulations of these two cations paired with hexafluorophosphate in the pure st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

82
1,273
4
14

Year Published

2007
2007
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 1,412 publications
(1,373 citation statements)
references
References 29 publications
82
1,273
4
14
Order By: Relevance
“…This scenario also applies to the OCS- [Bmim] [Ac]. It remains to understand why the presence of imidazolium-dithiocarboxylate was not observed in CS 2 …”
Section: Interpretation and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This scenario also applies to the OCS- [Bmim] [Ac]. It remains to understand why the presence of imidazolium-dithiocarboxylate was not observed in CS 2 …”
Section: Interpretation and Discussionmentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8][9][10][11] In this context, imidazolium acetate based ILs were proposed as systems able to capture comparatively to other ionic liquids, unusual amounts of carbon dioxide. 12,13 A number of investigations by us and others have shown that carbon dioxide dissolved in dried 1-butyl-3-methylimidazolium acetate [Bmim] [Ac] a) Author to whom correspondence should be addressed.…”
Section: Introductionmentioning
confidence: 99%
“…The large entropic effect led to a negative deviation from the ideal solubility that might explain why CO 2 is more soluble in the larger 1-decyl-than in the smaller 1-ethyl-3-methylimidazolium IL`s (Cadena et al, 2004;Anthony et al, 2005).…”
Section: Brazilian Journal Of Chemical Engineeringmentioning
confidence: 99%
“…CO2 can act as both Lewis acid and Lewis base. The CO2 solvation is initiated by some carboxylation reaction at the C2 position of the imidazolium ring [5]. Besides, the ether functionality helps in CO2 capture whereby the lone pair of electrons present on the oxygen atom takes part in nucleophilic attack with the carbon atom on CO2 [4].…”
Section: Introductionmentioning
confidence: 99%